1973
DOI: 10.1139/y73-063
|View full text |Cite|
|
Sign up to set email alerts
|

An Intracellular Study of the Actions of Carbon Dioxide on the Spinal Monosynaptic Pathway

Abstract: The actions of CO2 were studied on 48 lumbosacral motoneurones impaled with microelectrodes in spinal cats. CO2 produced a reversible depolarization in some cells tested and a reversible hyper-polarization in other cells tested. Both increases and decreases in membrane resistance were produced by CO2, and these were significantly correlated with hyperpolarizations and depolarizations of the membrane, respectively. The after-hyperpolarization following an antidromic response was always reduced by CO2, irrespect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Similarly, the depression of synaptic transmission noted during perfusion with low-HC03-ACSF and its enhancement during perfusion with high-HC03-ACSF have been previously described both in vivo and in vitro during alterations in pH0 (Esplin et al 1973;Caspers & Speckmann, 1974;Balestrino & Somjen, 1988). These effects therefore probably largely reflect changes in pHo rather than being a specific consequence of changes in [HC03-j0, although confirmation of this possibility awaits intracellular experiments in which pHo is altered by other means.…”
Section: Epileptiform Activity In High-hc03-acsfsupporting
confidence: 57%
See 2 more Smart Citations
“…Similarly, the depression of synaptic transmission noted during perfusion with low-HC03-ACSF and its enhancement during perfusion with high-HC03-ACSF have been previously described both in vivo and in vitro during alterations in pH0 (Esplin et al 1973;Caspers & Speckmann, 1974;Balestrino & Somjen, 1988). These effects therefore probably largely reflect changes in pHo rather than being a specific consequence of changes in [HC03-j0, although confirmation of this possibility awaits intracellular experiments in which pHo is altered by other means.…”
Section: Epileptiform Activity In High-hc03-acsfsupporting
confidence: 57%
“…These findings may at least in part reflect a reduction in afferent fibre excitability (e.g. see Morris, 1971;Esplin et al 1973), although more recently Balestrino & Somjen (1988) have suggested that the main effect of a reduction in pHo on excitability in the hippocampus is on postsynaptic neurones, not synaptic drive. Experiments conducted with ionophoretically applied excitatory amino acids (see below) also demonstrate a change in postsynaptic excitability.…”
Section: Synaptically Evoked Potentialsmentioning
confidence: 99%
See 1 more Smart Citation
“…This "dissociation" of blood flow and activity may have a physiological significance. Elevated CO 2 partial pressure is known to depress synaptic efficacy (Esplin et al, 1973), and thus enhanced circulatory convection associated with activity beyond the limits required to adjust energy substrates supplies to energy demand, may help preserve or enhance synaptic function by washing out tissue CO 2 . The existence of feed-forward rather than feed-back mechanisms of CBF control is also supported by the fact that during the initial phase of convulsive seizures, CBF increases several fold in the cerebral cortex, and simultaneous records of tissue pH not only fail to show a metabolic error signal (acidification) but indicate tissue alkalosis instead, due to washout of CO 2 by enhanced circulatory convection (Astrup et al, 1978).…”
Section: Functional Localization With Blood Flowmentioning
confidence: 99%
“…In the peripheral nervous system, somatosensory function is also known to be depressed by elevated CO 2 without affecting spinal motorneurons (Krnjevic et al 1965). A study examining the intracellular actions of CO 2 on the spinal monosynaptic pathway concluded that ''the principle action of CO 2 is to block conduction in the intraspinal branches of the afferent fibers'' (Esplin et al 1973). The present findings agree with these observations in that afferent transmission appears to be reduced, but spinal integration and efferent function are not affected.…”
Section: Skeletal Muscle Contractile Functionmentioning
confidence: 99%